Dynamics of Multiple Identity and Self-Presentation of Generation Z Students in Jakarta on Social Media - Hanan, Muhamad Afham; Hariyati, Farida; Agustini, Vilya Dwi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The purpose of this research is to examine how Jakartan Generation Z students utilize cross-platform social media and the dynamics of numerous identities and self-presentation techniques. Data was gathered through in-depth interviews with eight informants and social media account content analysis using a qualitative approach and case study methodology. Through the use of several accounts, content curating techniques, and the division of responsibilities between front and back stages, the results demonstrate that students actively control their digital identities. This occurrence demonstrates the applicability of Goffman's theory of dramaturgy in elucidating the performance of digital identities in relation to the audience and social milieu. There is a notable contrast between online and offline representations, as seen by the unique finding of one informant who portrayed himself as outgoing on social media but remained introverted in real life. According to the study's findings, Generation Z students' digital identities are strategic, dynamic, and reflective, with the goal of upholding both their public persona and their right to free speech. Opportunities for additional research to examine psychological and professional aspects in a wider context are presented by the study's limitations regarding the quantity and range of informants.